Boccia as a Rehabilitation Intervention for Adults With Severe Mobility Limitations Due to Neuromuscular and Other Neurological Disorders: Feasibility and Effects on Upper Limb Impairments - Suárez-Iglesias, David; Ayán Perez, Carlos; Mendoza-Laiz, Nuria; Villa-Vicente, José Gerardo (Frontiers in Psychology, 2020)
Purpose: Scant research exists regarding the effects of playing Boccia as a rehabilitation strategy for people with severe mobility limitations due to neuromuscular and other neurological disorders. This study is aimed at identifying the feasibility and effects of playing Boccia on the upper limb impairments of people with severe mobility limitations due to neuromuscular and other neurological disorders. Materials and Methods: Seven people played Boccia three times per week for 20 weeks as part of the rehabilitation process, while other seven kept up with their usual rehabilitation schedule. Attrition, adherence, adverse effects, participation and completion rate were registered to assess feasibility. The effects of the program on grip, pinch strength and upper-limb active range of motion were assessed by means of a dynamometer and a goniometer. Results and Conclusions: The program was feasible, although no effects were observed after its completion on variables assessed, except for hand flexion and ulnar deviation active range of motion. In a group of people with severe disability due to neuromuscular and other neurological disorders, playing Boccia as part of a multidisciplinary rehabilitation program was shown to be a feasible therapy. However, practicing this game did not lead to significant improvements in upper limb impairments, except for wrist flexion and ulnar deviation active range of motion.